2003
DOI: 10.1002/pssc.200303419
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between strain, optical and electrical properties of InN grown by MBE

Abstract: The evolution of structural, optical and electrical properties was investigated for thin InN layers on either GaN or AlN buffer layers. Up to a layer thickness around 1 µm a biaxial strain is present in the layers. On AlN buffers the InN layers relax faster than on GaN. Both the interface and the surface affect the electron carrier concentration essentially. Thus, only with layers exceeding a thickness of 1 µm electron densities below 10 18 cm -3 can be achieved. Optical spectroscopy indicates a band gap energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2003
2003
2006
2006

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 14 publications
3
23
0
Order By: Relevance
“…In fact the polarization fields do not directly produce free carriers, but rather facilitate charge transfer from localized donor or acceptor states [9]. If the InN films are In-face polarity in the direction towards the surface and therefore N-face polarity towards the InN/GaN interface, spontaneous polarization will give a sheet electron density of 0.5 × 10 13 cm −2 at the interface (see table 1), as previously stated by Cimalla et al [10]. As a result of the spontaneous polarization coefficient being greater for AlN than for InN, under the same conditions of N-polarity InN and Al-polarity AlN at the interface, there will be a hole gas at the interface due to spontaneous polarization, with a sheet density of 3.0 × 10 13 cm −2 .…”
Section: Resultsmentioning
confidence: 53%
“…In fact the polarization fields do not directly produce free carriers, but rather facilitate charge transfer from localized donor or acceptor states [9]. If the InN films are In-face polarity in the direction towards the surface and therefore N-face polarity towards the InN/GaN interface, spontaneous polarization will give a sheet electron density of 0.5 × 10 13 cm −2 at the interface (see table 1), as previously stated by Cimalla et al [10]. As a result of the spontaneous polarization coefficient being greater for AlN than for InN, under the same conditions of N-polarity InN and Al-polarity AlN at the interface, there will be a hole gas at the interface due to spontaneous polarization, with a sheet density of 3.0 × 10 13 cm −2 .…”
Section: Resultsmentioning
confidence: 53%
“…However, the InN sample (7.5 µm) has been shown to be fully relaxed by high-resolution transmission electron microscopy and reciprocal space mapping (RSM). In fact, studies show that in MBE grown InN film on GaN buffer layers the residual strain falls off quickly with thickness [5,6]. It has been reported that the InN films are fully relaxed after a few bilayers on GaN [5] or above 35 nm on sapphire [7] during growth.…”
Section: Resultsmentioning
confidence: 99%
“…The InN samples used in this study were grown by migration enhanced molecular beam epitaxy [4] on in situ prepared 220 nm Ga-face GaN buffer layers [1]. The structural and electrical properties of the layers were analysed by X-ray diffraction (XRD), Auger electron spectroscopy (AES), and Hall-measurements.…”
Section: Methodsmentioning
confidence: 99%
“…The recent improvements in the heteroepitaxial growth by molecular beam epitaxy [1] allowed the preparation of InN layers with carrier concentrations down to 10 17 cm -3 [2]. A conclusive model for the observed decreasing conductivity with increasing layer thickness is the confinement of a high carrier concentration at the interface to the substrate due to piezoelectric charges and at the surface due to doping by oxygen [3,4]. Up to date, attempts to prove the electron accumulation at the surface include C-Vprofiling [3], measurement of the sheet carrier density versus thickness [3], both accomplished on air, and high-resolution electron-energy-loss spectroscopy (HREELS) on clean InN surfaces in ultrahigh vacuum [5,6].…”
Section: Introductionmentioning
confidence: 98%